The Future of Global Neurosurgery and the Peshawar Declaration - Khan, Tariq; Khattak, Almas F.; Park, Kee B.; Rosseau, Gail; Qazi, Mustafa; Khan, Akif S. (WFNS Journal, 2025)
The Peshawar Declaration reinforces the critical need for equitable access to neurosurgical care, especially in the low- and middle-income countries (LMICs). With most of the people requiring neurosurgical care living in resource-constrained settings, the field faces significant challenges, such as a lack of trained neurosurgeons, poor infrastructure, and disparity in accessing care. The Peshawar Declaration presents a unified vision for addressing these gaps, building on previous efforts, including the Bogota Declaration (2016) and the establishment of the Global Neurosurgery Committee (2019).More than 800 people attended the Global Neurosurgery Conference 2024 in Peshawar, including neurosurgeons, policymakers, researchers, and patient advocates, to discuss the latest developments and challenges in neurosurgical care.The main outcome was the adoption of a unified definition of global neurosurgery encompassing both clinical practice and public health. The integration of neurosurgery into global health systems, capacity building, strategic partnerships, and the role of advocacy in policy formation were the key topics of debate. The declaration focused on national neurosurgical champions, task-sharing models, multidisciplinary collaboration, and young neurosurgeons' involvement in governance. For sustaining neurosurgical programs, the declaration calls for the development of advocacy toolkits, community-driven initiatives, and research-based residency tracks.The Peshawar Declaration calls on policymakers, healthcare professionals, and global health organizations to work together to reiterate the commitment to timely, safe, and equitable global neurosurgical care. The declaration sets the stage for sustainable progress in global neurosurgery by fostering an inclusive and collaborative approach.
Keywords: global neurosurgery; Peshawar declaration; advancement; future